The globalization of Malaysia national cuisine: a concept of 'Gastrodiplomacy' - Nahar, Naili; Ab Karim, Shahrim; Karim, Roselina; Mohd Ghazali, Hasanah; Krauss, Steven Eric (Universiti Teknologi MARA Malaysia (UiTM), 2018)
Malaysia national cuisines are inherited through various generations and have been created through multiple evolutions and assimilations, in which formed very unique and delicious cuisines using various tropical ingredients. However, Malaysia national cuisine is still new to some of the global citizens. Therefore, food globalization is very important, because food globalization not only contributes to the trade industries but also contributes to other local industries such as tourism industries. A new term known as 'gastrodiplomacy' has been introduced recently to explains how countries used their national cuisines as a method to promote their countries, cultures, foods, attract foreign tourists and also build political relations. Malaysia also has rigorously applying gastrodiplomacy practices especially through the 'Malaysia Kitchen for the World' programme (MKP). Not only that, media such as documentary programmes and cooking competitions somehow contributes to the globalization of Malaysia national cuisine. Though the government and the citizens have taken various actions, there are still rooms for improvements to make the cuisines further known worldwide. Malaysia has been recognized as one of the best gastrodiplomacy practitioners in the world, and it is hoped that this article could be as a platform to share how Malaysia used this method to promote its national cuisines.